Linux in a Windows world - Smith, Roderick W. (O'Reilly, 2005)
Linux's unparalleled functionality and adaptability have made it the main alternative to Unix and Microsoft Windows operating systems. And with good reason. System administrators realize that this robust alternative can greatly improve their operating system's reliability and save them money, too. Linux systems are even less vulnerable to attacks by computer viruses and worms. Not surprisingly, businesses, government agencies, schools, and a wealth of other institutions are all looking to Linux to replace the Windows desktop for these same benefits. Linux in a Windows World takes an in-depth look at exactly how Linux can be brought into an organization that's currently based on Microsoft Windows systems. Featuring a litany of insider tips and techniques, Linux in a Windows World dispenses all the practical advice you need to migrate to this revolutionary open source software. Author Roderick W. Smith, himself a renowned system administrator and Linux convert, understands that the skills required to install, deploy, and maintain Linux are not easy to find. That's why he has tapped the absolute best source of information available: the Linux server experts who have made it their life's work to build and manage the Linux system. The latest in O'Reilly's line of bestselling Linux titles, Linux in a Windows World is an invaluable companion for any system administrator interested in integrating Linux into their Windows environment.